Preparation method of fresh-keeping material based on nanocrystals

By combining plant-extract essential oil with nanocrystals, the porous structure and high specific surface area of ​​the nanocrystals can be used to achieve the coating and slow release of essential oils, which solves the problems of uncontrolled release of essential oils and poor antibacterial effects in existing food packaging materials, and achieves higher stability and fresh preservation performance.

CN119639044APending Publication Date: 2025-03-18HUAZHONG AGRI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411937702.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Among the existing food packaging materials, volatile plant-extract essential oil has poor dispersion, uncontrolled release, poor antibacterial effect, and poor stability.

Method used

Using nanocrystal-based fresh preservation material preparation method, the composite membrane is prepared by combining plant-extract essential oil with nanocrystals (such as ZIF-8 and CEO), using the porous structure and high specific surface area of ​​the nanocrystals to achieve the coating and slow release of essential oils, and the nanocrystal precipitates are obtained through magnetic stirring and centrifugation treatment, and finally mixed with materials such as polyvinyl alcohol and calcium chloride to prepare a composite membrane.

Benefits of technology

It improves the stability and antibacterial effect of plant extract essential oils, extends the acting time of essential oils, enhances the fresh preservation performance of packaging materials, and has an indication function.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119639044A_ABST
    Figure CN119639044A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a preservation material based on nanocrystals, and belongs to the field of food packaging.The method comprises the steps that zinc nitrate hexahydrate is dissolved in deionized water to obtain an aqueous solution, 2-methylimidazole is dissolved in methyl alcohol to obtain a methyl alcohol solution, plant extract essential oil is added into the methyl alcohol solution, and the mixture is stirred to be uniform; fully dissolving the aqueous solution and the methanol solution respectively; dropwise injecting the aqueous solution into a methanol solution, magnetically stirring sufficiently, performing centrifugal treatment to obtain a precipitate, washing the precipitate for several times, and freeze-drying to obtain a nanocrystal; adding polyvinyl alcohol into distilled water, stirring until the polyvinyl alcohol is completely dissolved, then adding glycerol as a plasticizer, and continuously stirring to obtain a polyvinyl alcohol solution; the preparation method comprises the following steps: adding nanocrystals into a polyvinyl alcohol solution, fully mixing, adding calcium chloride and distilled water, fully stirring to obtain a film-forming solution, pouring the film-forming solution into a polystyrene culture dish, and drying to obtain the composite film. The composite film is good in dispersity, long in action time of plant extract essential oil, high in stability and stronger in antibacterial effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of food packaging, and in particular to a method for preparing a nanocrystal-based fresh-keeping material. Background Art

[0002] Food packaging usually requires that the packaging film has good oxygen barrier and waterproof properties to prevent the packaged food from being oxidized and damp, which may lead to food spoilage. Plant essential oils have antibacterial effects, and many essential oils contain ingredients that can inhibit bacterial growth, such as tea tree essential oil, which can effectively inhibit a variety of bacteria. Volatile plant essential oils can be added to preservative materials.

[0003] However, the dispersion in hydrophobic material membranes is currently poor, the release of volatile plant essential oils cannot be controlled, and it is difficult to ensure effectiveness. Plant essential oils usually have poor light and thermal stability and are easily oxidized, resulting in poor stability. In addition, a single plant essential oil has poor antibacterial properties. Summary of the invention

[0004] In view of the problems existing in the prior art, the present invention provides a method for preparing a fresh-keeping material based on nanocrystals.

[0005] The invention provides a method for preparing a fresh-keeping material based on nanocrystals, comprising: dissolving zinc nitrate hexahydrate in deionized water to obtain an aqueous solution, dissolving 2-methylimidazole in methanol to obtain a methanol solution, adding plant essential oil to the methanol solution, and fully dissolving the aqueous solution and the methanol solution respectively; dripping the aqueous solution into the methanol solution, stirring magnetically and then centrifuging to obtain a precipitate, washing the precipitate for several times and then freeze-drying to obtain nanocrystals; adding polyvinyl alcohol into distilled water, stirring until completely dissolved, and then adding glycerol as a plasticizer and continuously stirring to obtain a polyvinyl alcohol solution; adding the nanocrystals into the polyvinyl alcohol solution, mixing fully, adding calcium chloride and distilled water, stirring fully to obtain a film-forming liquid, and pouring the film-forming liquid into a polystyrene culture dish to dry to obtain a composite film.

[0006] According to a method for preparing a nanocrystal-based fresh-keeping material provided by the present invention, the plant-extracted essential oil includes clove essential oil.

[0007] According to a method for preparing a nanocrystal-based fresh-keeping material provided by the present invention, the method further comprises adding curcumin to the polyvinyl alcohol solution before adding calcium chloride and distilled water after the sufficient mixing.

[0008] According to a method for preparing a nanocrystal-based fresh-keeping material provided by the present invention, the step of fully dissolving the aqueous solution and the methanol solution comprises: ultrasonically treating the aqueous solution and the methanol solution at room temperature respectively until the solutions are fully dissolved.

[0009] According to a method for preparing a nanocrystal-based fresh-keeping material provided by the present invention, washing the precipitate several times comprises: washing the precipitate several times with methanol.

[0010] According to a method for preparing a nanocrystal-based fresh-keeping material provided by the present invention, before the film-forming liquid is poured into a polystyrene culture dish for drying, the method further comprises: ultrasonically treating the film-forming liquid at room temperature to remove bubbles in the solution and to evenly disperse the components.

[0011] According to a method for preparing a nanocrystal-based fresh-keeping material provided by the present invention, the mass percentage of the glycerol comprises 30% of the polyvinyl alcohol.

[0012] According to a method for preparing a nanocrystal-based fresh-keeping material provided by the present invention, the mass ratio of curcumin comprises 0.5-1.5% of polyvinyl alcohol.

[0013] According to a method for preparing a fresh-keeping material based on nanocrystals provided by the present invention, the nanocrystals are added to the polyvinyl alcohol solution, and the mass ratio of the nanocrystals is 3% to 7% of the polyvinyl alcohol.

[0014] According to a method for preparing a nanocrystal-based fresh-keeping material provided by the present invention, the mass ratio of calcium chloride comprises 4% of polyvinyl alcohol.

[0015] The method for preparing a fresh-keeping material based on nanocrystals provided by the present invention has the advantages that after being loaded by a metal organic framework, the nanocrystals obtained are tiny, have good dispersibility, and are dispersed relatively evenly in a polymer solution; due to the porous and high specific surface area characteristics of the nanocrystals, the encapsulation of plant essential oils can be achieved, and the encapsulated plant essential oils are slowly released from the pores, so that the action time of the plant essential oils is greatly extended; after being loaded by the nanocrystals, the plant essential oils have a layer of crystal shell, which has a protective effect and high stability; since the nanocrystals also have a strong antibacterial effect, the antibacterial effect of the encapsulated plant essential oils is enhanced, which can better meet actual needs. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0017] Figure 1 It is a schematic diagram of the process of preparing the nanocrystal-based fresh-keeping material provided by the present invention;

[0018] Figure 2This is one of the performance display diagrams of ZIF-8&CEO nanocrystals provided by the present invention;

[0019] Figure 3 This is the second performance display diagram of ZIF-8&CEO nanocrystals provided by the present invention;

[0020] Figure 4 This is one of the performance display diagrams of the composite membrane provided by the present invention;

[0021] Figure 5 This is the second performance display diagram of the composite membrane provided by the present invention;

[0022] Figure 6 It is a graph showing the results of the freshness-keeping test of the composite film provided by the present invention. DETAILED DESCRIPTION

[0023] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the drawings of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] Combine the following Figure 1-Figure 6 The invention describes a method for preparing a nanocrystal-based fresh-keeping material. Figure 1 is a schematic diagram of a process for preparing a nanocrystal-based fresh-keeping material provided by the present invention, such as Figure 1 As shown, the present invention provides a method for preparing a fresh-keeping material based on nanocrystals, comprising:

[0025] 101. Dissolve zinc nitrate hexahydrate in deionized water to obtain an aqueous solution, dissolve 2-methylimidazole in methanol to obtain a methanol solution, add plant essential oil to the methanol solution, and fully dissolve the aqueous solution and the methanol solution, respectively.

[0026] In one embodiment, the plant essential oil includes clove essential oil (CEO).

[0027] Taking clove essential oil as an example of plant essential oil, firstly, zinc nitrate hexahydrate (560 mg) and 2-methylimidazole (660 mg) are dissolved in deionized water and methanol respectively, and 720 mg of clove essential oil is added to the methanol solution.

[0028] In one embodiment, the fully dissolving the aqueous solution and the methanol solution respectively comprises: ultrasonically treating the aqueous solution and the methanol solution respectively at room temperature until the solutions are fully dissolved.

[0029] For example, the deionized water and methanol solution may be sonicated at a power of 200 W for 10 min at room temperature to ensure that the solution is fully dissolved.

[0030] 102. The aqueous solution is dripped into the methanol solution, and after sufficient magnetic stirring, centrifugation is performed to obtain a precipitate, and the precipitate is washed several times and then freeze-dried to obtain nanocrystals.

[0031] In one embodiment, washing the precipitate several times comprises: washing the precipitate several times with methanol.

[0032] For example, the aqueous solution can be injected into the methanol solution with a syringe at room temperature and stirred magnetically for 10 minutes. Finally, the resulting solution is centrifuged (4°C, 8000 rpm, 10 minutes), and the resulting precipitate is washed three times with methanol and then freeze-dried to obtain ZIF-8 & CEO nanocrystals. In addition, the product synthesized according to the above method but without adding CEO is ZIF-8 nanocrystals.

[0033] 103. Add polyvinyl alcohol into distilled water, stir until completely dissolved, then add glycerol as a plasticizer and continue stirring to obtain a polyvinyl alcohol solution.

[0034] In one embodiment, the ratio of polyvinyl alcohol in the polyvinyl alcohol (PVA) solution is 60 mg / ml. In one embodiment, the mass percentage of glycerol is 30% of the polyvinyl alcohol.

[0035] For example, 600 mg of PVA can be added to 10 mL of distilled water and stirred (300 rpm) for 3 h in a water bath heated at 90° C. After the PVA is completely dissolved, the solution is naturally cooled to 40° C., and glycerol (30% w / w of PVA) is added as a plasticizer, and stirring is continued for 10 min to obtain a polyvinyl alcohol solution.

[0036] 104. Add the nanocrystals to the polyvinyl alcohol solution, add calcium chloride and distilled water after thorough mixing, stir thoroughly to obtain a film-forming solution, pour the film-forming solution into a polystyrene culture dish and dry it to obtain a composite film.

[0037] In one embodiment, before the film-forming solution is poured into a polystyrene petri dish and dried, the process further comprises: subjecting the film-forming solution to ultrasonic treatment at room temperature to remove air bubbles in the solution and to uniformly disperse the components. In one embodiment, the mass ratio of calcium chloride is 4% of polyvinyl alcohol.

[0038] In one embodiment, the method further comprises adding curcumin to the polyvinyl alcohol solution before adding calcium chloride and distilled water after the thorough mixing.

[0039] In the embodiment of the present invention, curcumin can be added as a color indicator. Under the joint action of the natural pigment-curcumin and the nanocrystals, the composite film has the dual functions of preservation and indication, wherein the nanocrystals are responsible for providing the preservation effect, and the curcumin has the indication effect.

[0040] For example, curcumin and ZIF-8&CEO nanocrystals were added to the above solution, and the mixed solution was stirred at 300 rpm and 40°C for 5 min. After thorough mixing, calcium chloride (4.0% w / w of PVA) and distilled water were added to the solution and stirred for 5 min to finally obtain 20 mL of film-forming solution. The film-forming solution was then ultrasonicated (200 W) at room temperature for 3 min to remove bubbles in the solution and to evenly disperse the components.

[0041] In one embodiment, pouring the membrane-forming liquid into a polystyrene culture dish and drying it comprises: pouring the membrane-forming liquid into a polystyrene culture dish and drying it at 40° C. for 12 hours.

[0042] That is, finally, pour the film-forming liquid into a polystyrene culture dish (the diameter may be 90 mm), dry it at 40° C. for 12 hours, and obtain a dried composite membrane.

[0043] The method for preparing a fresh-keeping material based on nanocrystals in an embodiment of the present invention is that the nanocrystals obtained after being loaded by a metal organic framework are tiny, have good dispersibility, and are dispersed more evenly in a polymer solution. Due to the porous and high specific surface area characteristics of the nanocrystals, the coating of plant essential oils can be achieved, and the coated plant essential oils are slowly released from the pores, so that the action time of the plant essential oils is greatly extended. Plant essential oils usually have the characteristics of poor light stability and thermal stability and easy oxidation. After being loaded with nanocrystals, the plant essential oils have a layer of crystal shell, which has a protective effect and high stability. After being embedded in the nanocrystals, since the nanocrystals also have a strong antibacterial effect, the antibacterial effect of the embedded plant essential oils is enhanced, which can better meet actual needs. Under the joint action of natural pigment-curcumin and nanocrystals, the composite film has the dual functions of fresh-keeping-indication, in which the nanocrystals are responsible for providing the fresh-keeping effect, and curcumin has the indication effect.

[0044] In one embodiment, the mass ratio of curcumin is 0.5-1.5% of polyvinyl alcohol. In one embodiment, the polyvinyl alcohol solution is added to the nanocrystals, and the mass ratio of the nanocrystals is 3% to 7% of the polyvinyl alcohol.

[0045] For comparison, ZIF-8 nanocrystals were obtained without adding CEO in 103. Meanwhile, curcumin was added to the above solution at 0.5%, 1.0% and 1.5% w / w of PVA and ZIF-8 & CEO nanocrystals were added to PVA at 3.0%, 5.0% and 7.0% w / w.

[0046] The numbers and formulas of all composite films are shown in the following table.

[0047]

[0048]

[0049] Performance test of nanocrystals:

[0050] First, for the microscopic morphology of ZIF-8 and ZIF-8&CEO nanocrystals, a field emission scanning electron microscope (FE-SEM, CLARA, TESCAN, Czech Republic) was used to capture the morphological images of the nanocrystals under the condition of a beam energy of 20 kV, and the samples were sprayed with gold before observation. The particle size distribution of the nanocrystals was then obtained using the software ImageJ. In addition, a transmission electron microscope (TEM, HITACHI, H-7650, Japan) was used to further observe the internal structure and morphology of the nanocrystals. When preparing the sample, a small amount of the suspension was first loaded onto a copper grid, then dried, and then imaged.

[0051] Results (corresponding to Figure 2 Aj, ab, and cd in the figure are FE-SEM images of ZIF-8 and ZIF-8&CEO, ef and gh are TEM images of ZIF-8 and ZIF-8&CEO, and i and j are particle sizes of ZIF-8 and ZIF-8&CEO, respectively): ZIF-8 nanocrystals present a uniform rhombic dodecahedral structure with a particle size of about 67nm, indicating that ZIF-8 nanocrystals are successfully synthesized. Compared with ZIF-8 nanocrystals, it is obviously observed that the particle size of ZIF-8&CEO nanocrystals increases (about 138nm), which is because CEO is effectively filled into the hollow cavity of ZIF-8. In the image of ZIF-8&CEO nanocrystals, it is also observed that some crystals are spherical, and the particle size is significantly larger than other crystals with regular morphology, but the regular morphology of ZIF-8 nanocrystals can still be observed inside through transmission electron microscopy, which is due to the surface of ZIF-8 nanocrystals covered by CEO. The above results all show that ZIF-8&CEO nanocrystals are successfully synthesized.

[0052] Crystal structure of nanocrystals: The crystal structure of ZIF-8 and ZIF-8&CEO nanocrystals was determined by X-ray diffractometer (D8 advance, Bruker AXS, Germany). Cu Kα radiation ( 40 kV, 40 mA), the scan rate was 4° / min, and the 2θ range was 5–40°.

[0053] result( Figure 2 (k is the XRD spectrum): It can be clearly observed in the spectrum that the characteristic peak positions of ZIF-8 and ZIF-8&CEO nanocrystals are consistent and completely match the simulated spectrum of ZIF-8. This shows that the addition of CEO does not affect the crystal structure of ZIF-8. It is worth noting that compared with ZIF-8, the characteristic peak intensity of ZIF-8&CEO nanocrystals near 2θ=7.3° is significantly reduced, which may be due to the surface of ZIF-8 being covered by CEO.

[0054] Thermogravimetric analysis of nanocrystals: Thermogravimetric analysis (TGA) spectra of ZIF-8 and ZIF-8&CEO nanocrystals were obtained by thermogravimetric analyzer (Q600 SDT, TA Instruments, USA). Specifically, about 5 mg of nanocrystal powder was placed in a standard aluminum pan, and then the temperature was increased to 600 ° C at a heating rate of 10 ° C / min under a nitrogen flow of 50 mL / min, and the weight change of the sample during this period was recorded.

[0055] Nanocrystal loading rate of clove essential oil: The loading rate of ZIF-8&CEO nanocrystals was evaluated by absorbance method. First, a mixed solution of 32mL of anhydrous ethanol and 2mL of acetic acid was prepared, and 100mg of ZIF-8&CEO nanocrystals were dispersed in the mixed solution and magnetically stirred (300rpm) at room temperature for 30 minutes. Then the filtrate was collected by centrifugation (4°C, 8000rpm, 10min) and washed three times with 2mL of anhydrous ethanol. Finally, the absorbance (A) value at 279nm was measured using a UV spectrophotometer (UH5300, Hitachi, Japan). The CEO concentration in the filtrate was determined according to the following standard curve:

[0056] A=0.0157C+0.0586(R 2 =0.9992)#(1)

[0057] Here A is the absorbance and C is the concentration of CEO (nL / mL).

[0058] The loading rate of ZIF-8&CEO nanocrystals on CEO is calculated according to the following formula:

[0059]

[0060] Here c is the concentration of CEO in the filtrate (nL / mL), v is the volume of the filtrate (mL), f is the dilution factor of the filtrate, and m is the total mass of the nanocrystals (mg).

[0061] Results (corresponding to Figure 2 Part 1): The LC of CEO in ZIF-8&CEO was measured by colorimetry to be 19.10±1.30%. Thermogravimetric analysis (TGA) of ZIF-8 and ZIF-8&CEO nanocrystals was also performed, and the results are as follows Figure 2 As shown. The curve of ZIF-8 nanocrystals shows a sharp drop in mass at 255°C, which may be caused by the evaporation of residual water molecules in the ZIF-8 cavity. The curve of ZIF-8&CEO nanocrystals shows obvious mass loss from 145°C and continues until 600°C. Finally, there is a weight difference of about 19.6% with ZIF-8, which is mainly attributed to the thermal degradation of CEO loaded in the nanocrystals. And the weight difference is basically consistent with the LC value measured by colorimetry.

[0062] Fourier transform infrared spectra of ZIF-8 and ZIF-8&CEO nanocrystals were obtained using a Fourier transform infrared spectrometer (Nicolet iS10, Thermo Scientific, America) in the range of 400–4000 cm -1 Fourier transform infrared spectra over the spectral range.

[0063] Results (corresponding to Figure 2 m): In the FTIR spectrum of CEO, the absorption peak at 3524 cm-1 corresponds to the stretching vibration of OH. -1 The absorption peaks are the stretching vibration of CH, 1606, 1509 and 1430 cm -1 The peaks at 1033 and 915 cm are related to the C=C stretching vibrations in the aromatic ring. -1 The peaks at 3135 and 2925 cm are related to the bending vibration of OH. -1 The absorption peaks at 1580, 1146 and 994 cm-1 correspond to the aromatic and aliphatic CH stretching vibrations in dimethylimidazole, respectively. -1The peak at 3524cm corresponds to the stretching vibration of C=N and CN. After encapsulating CEO in ZIF-8, the absorption peak intensity of CEO significantly weakened or even disappeared, indicating that CEO has been successfully encapsulated in the structure of ZIF-8. The spectrum of ZIF-8&CEO nanocrystals is similar to that of ZIF-8 in terms of characteristic peak positions. However, in the spectrum of ZIF-8&CEO, the original CEO at 3524cm -1 The OH characteristic peak at 3550 cm -1 , and 2925cm -1 The absorption peak intensity at is enhanced, indicating the existence of hydrogen bonding between CEO and ZIF-8. In addition, no new characteristic peaks appear in the spectrum of ZIF-8&CEO, which means that no new chemical reaction occurs during the encapsulation process, and CEO is encapsulated mainly through physical adsorption and hydrogen bonding. This phenomenon ensures the chemical stability of the composite nanocrystals.

[0064] Thermal stability of nanocrystals: The thermal stability of CEO in ZIF-8 & CEO nanocrystals was determined. Specifically, 100 mg of CEO and 100 mg of freshly prepared nanocrystal freeze-dried powder were incubated in a constant temperature water bath at 70, 80 and 90 °C, respectively, in the dark for 10 h. After the samples were cooled to room temperature, the retention of CEO was measured using the method described in the loading rate of nanocrystals on clove essential oil, and the retention rate of CEO was calculated according to the following formula:

[0065]

[0066] Results (corresponding to Figure 3 Middle a): After heating at 70℃, 80℃ and 90℃ for 10 hours, the retention rates of CEO in ZIF-8&CEO nanocrystals were 49.18%, 37.74% and 25.54%, respectively. In contrast, the retention rates of free CEO under the same conditions were significantly reduced, namely 37.38%, 9.67% and 1.04%, respectively. This indicates that the retention rate of CEO in ZIF-8&CEO nanocrystals after heat treatment is significantly higher than that of free CEO. ZIF-8&CEO nanocrystals provide a confined nanoscale environment for CEO, effectively delaying the thermal degradation process of CEO, thereby significantly enhancing the thermal stability of CEO under high temperature conditions.

[0067] Antioxidant activity of nanocrystals: The in vitro antioxidant activity of nanocrystals was determined using the DPPH and ABTS methods. First, ZIF-8 methanol dispersion, ZIF-8&CEO methanol dispersion, and CEO methanol solution were prepared as test solutions at a concentration of 1 mg / mL. A certain amount of DPPH was dissolved in methanol to prepare a 0.1 mM DPPH solution, and then 1 mL of the test solution was added to 4 mL of DPPH solution and incubated in the dark for 30 minutes. After incubation, centrifuge (8000 rpm, 4°C, 10 min), collect the supernatant, and measure the absorbance of the solution at 517 nm using a UV spectrophotometer. An equal concentration of ascorbic acid was used as a positive control.

[0068] The DPPH scavenging ability of the sample was calculated according to the following formula:

[0069]

[0070] Here is the absorbance of a mixed solution of 1 mL sample and 4 mL DPPH, It is the absorbance of a mixed solution of 1 mL methanol and 4 mL DPPH.

[0071] The ABTS scavenging ability of the samples was also tested. In short, 7.4mM ABTS aqueous solution and 2.6mM potassium persulfate aqueous solution were mixed in equal proportions at room temperature and incubated in the dark for 12h. The ABTS working solution was then diluted with methanol until the absorbance at 734nm was 0.70. Then 0.3mL of the test solution was mixed with 4.7mL of methanol solution and incubated in the dark for 6min, and then its absorbance was measured at 734nm. Equal concentrations of ascorbic acid were also used as positive controls. The ABTS scavenging ability of the sample was calculated according to the following formula:

[0072]

[0073] Here is the absorbance of a mixed solution of 0.3 mL sample and 4.7 mL ABTS, It is the absorbance of a mixed solution of 0.3 mL methanol and 4.7 mL ABTS.

[0074] Results (corresponding to Figure 3 bc): The antioxidant activities of ZIF-8, free CEO and ZIF-8&CEO nanocrystals were compared using DPPH and ABTS. Figure 3). Among them, the scavenging ability of ZIF-8 is relatively poor (<5%). In contrast, free CEO and ZIF-8&CEO nanocrystals showed strong scavenging ability. The scavenging ability of 1mg / mL ZIF-8&CEO nanocrystals is >27 times that of ZIF-8 nanocrystals. The above results show that ZIF-8&CEO nanocrystals have strong antioxidant activity, and its antioxidant activity is related to the loading of CEO.

[0075] Antibacterial effect of nanocrystals: Minimum inhibitory concentration (MIC) refers to the lowest dose of a drug that can significantly inhibit the growth of a specific microorganism. The antibacterial properties and MIC of ZIF-8, ZIF-8&CEO nanocrystals and CEO were determined according to the following method. Specifically, the bacteria were cultured to the exponential growth phase (OD 600 =0.5), then the bacterial solution was washed with saline and diluted to 10 8 CFU / mL. Then 100μL of bacterial solution was evenly spread on a sterile nutrient agar plate, and a sterile filter paper (6mm in diameter) was placed in the culture dish. 6μL of samples of different concentrations (1.25mg / ml, 2.5mg / ml, 5mg / ml, 10mg / ml, 20mg / ml) were injected onto the filter paper. The culture dish was inverted and placed in a 37℃ incubator. After incubation for 24h, the diameter of the inhibition zone was measured using a digital vernier caliper, and the inhibition zone of the filter paper was observed at the same time until the previous concentration of the sample concentration without an inhibition zone appeared, which was the MIC.

[0076] Results (corresponding to Figure 3 d): Using Escherichia coli and Staphylococcus aureus as model strains, the antibacterial ability of ZIF-8, free CEO and ZIF-8&CEO nanocrystals at a concentration of 20 mg / mL was evaluated. Free CEO showed significant antibacterial activity against Escherichia coli and Staphylococcus aureus, with inhibition zone diameters of 8.07 mm and 6.72 mm, respectively. Studies have shown that clove essential oil (CEO) exerts its antibacterial effect by destroying cell walls and cell membranes, inhibiting the formation of biofilms, and hindering DNA synthesis. The inhibition zone diameters of ZIF-8 nanocrystals against Escherichia coli and Staphylococcus aureus were 12.92 mm and 11.12 mm, respectively. ZIF-8 exhibits significant antibacterial properties because it acidolyzes and releases zinc ions under slightly acidic conditions. These zinc ions interact with proteins or lipids in the cell membrane, leading to cell membrane destruction and eventual cell apoptosis. The diameters of the inhibition zones of ZIF-8 & CEO nanocrystals against Escherichia coli and Staphylococcus aureus were 17.35 mm and 13.89 mm, respectively. This indicates that the combination of ZIF-8 and CEO exhibits a significantly enhanced antibacterial effect, which may be due to the synergistic effect between the two.

[0077] In order to further quantitatively analyze the antibacterial properties of nanocrystals, the present invention determined the minimum inhibitory concentration (MIC) of ZIF-8, free CEO and ZIF-8&CEO nanocrystals to evaluate their effective antibacterial activity. Figure 3 As shown, ZIF-8&CEO nanocrystals showed the best effect in the MIC test of Escherichia coli and Staphylococcus aureus, both of which were 1.25 mg / mL. This shows that the complex can significantly inhibit the growth of these two strains at lower concentrations. The MIC value of ZIF-8 nanocrystals is 2.50 mg / mL. Compared with ZIF-8, ZIF-8&CEO nanocrystals have significantly enhanced inhibitory effects on Escherichia coli and Staphylococcus aureus. The MIC values ​​of free CEO are 10.00 mg / mL (Escherichia coli) and 20.00 mg / mL (Staphylococcus aureus), respectively. These results further support the synergistic effect between ZIF-8 and CEO, indicating that the combination of the two has significant advantages in enhancing antibacterial properties.

[0078] In summary, CEO-loaded ZIF-8 nanocrystals exhibited strong antibacterial effects in vitro, providing solid support for the application of nanomaterials in the packaging field, especially in the development of packaging materials with antibacterial properties.

[0079] Performance test of composite membrane:

[0080] Thickness of composite film: The thickness of composite film was measured using a digital micrometer (Mitutoyo, Japan). Specifically, five points were randomly selected on the composite film to measure their thickness, and the average value of these data was calculated and regarded as the thickness of the composite film.

[0081] Results (corresponding to Figure 4 (a) The addition of curcumin and an appropriate amount of ZIF-8&CEO nanocrystals did not significantly affect the thickness of the composite film. However, when the addition amount of ZIF-8&CEO reached 7% (w / w), the thickness of the composite film increased from 115μm (PVAfilm) to 128μm.

[0082] Color of composite film: L, a, b values ​​and whiteness index are used as color parameters of composite film. Simply put, three points are randomly selected on each composite film, and L, a and b values ​​are measured using CR400 colorimeter (Minolta, Japan). The WI of the composite film is calculated according to the following formula:

[0083]

[0084] Among them, L represents brightness, and a and b represent chromaticity coordinates.

[0085] Results (corresponding to Figure 4 Middle b): Pure PVA film presents a colorless and transparent appearance. With the addition of curcumin, the composite film turns yellow significantly. And with the increase of curcumin addition, the yellow color of the composite film deepens, and L, a, b and WI change significantly (p<0.05). This is because the inherent color of curcumin causes the color of the composite film to change. It is worth noting that the addition of ZIF-8&CEO nanocrystals makes the color of the composite film red, L, b and WI decrease significantly (p<0.05), and the a value increases significantly (p<0.05). When the amount of nanocrystals added is increased to 5% (w / w), the red color of the composite film deepens. This may be due to the interaction between ZIF-8&CEO nanocrystals and curcumin molecules, which changes the electronic structure of turmeric and thus changes its light absorption characteristics, resulting in a color change of curcumin from yellow to red. When the addition amount continues to increase to 7%, the color of the composite film does not change significantly.

[0086] UV-visible light blocking properties and opacity of the composite films: The UV-visible spectra of the composite films were measured in the range of 200 to 800 nm using a UV-visible spectrophotometer (UH5300, Hitachi, Japan). Air was used as a blank sample. The opacity of the composite film was calculated according to the following formula:

[0087]

[0088] Among them A 600 is the absorbance of the composite film at a wavelength of 600 nm, and d is the thickness of the film.

[0089] Results (corresponding to Figure 4 c): In practical applications, composite films need to protect food from direct light that would cause photodegradation and discoloration. Therefore, in this study, the light barrier properties and opacity of the composite films were measured. Figure 4 As shown, the pure PVA film has a high transmittance in the ultraviolet and visible light regions, and a low opacity, indicating that its light blocking performance is poor. The addition of curcumin reduces the transmittance of the composite film in both the ultraviolet and visible light regions, and improves the opacity. And with the increase in the amount of curcumin added, the transmittance further decreases and the opacity further increases. This is because the chromophores in curcumin have the ability to effectively absorb light radiation. The addition of ZIF-8&CEO nanocrystals also causes the light blocking performance of the composite film to produce the same trend of change. It is worth noting that the addition of an appropriate amount of curcumin and nanocrystals makes the composite film have a lower transmittance at 200-400nm. These results show that the addition of curcumin and nanocrystals can significantly enhance the light blocking ability of the composite film while also having a certain degree of transparency, which meets the needs of practical applications.

[0090] Microstructure of the composite film: A field emission scanning electron microscope (CLARA, TESCAN, Czech Republic) was used to obtain the surface and cross-sectional micromorphological images of the composite film. The cross-sectional samples were obtained by liquid nitrogen brittle fracture. All samples were gold-sprayed before observation, and the images were captured at 1,000× and 3,000× magnifications under an accelerating voltage of 5 kV.

[0091] Results (corresponding to Figure 5 (a-c): The surface of the pure PVA film is smooth and uniform, the cross section is dense, and there are no obvious pores. The introduction of curcumin (0.5-1.5% w / w) did not affect the microscopic morphology of the composite film, which indicates that curcumin has good dispersion in the PVA network structure, and the uniform coloring of the PVA-1.5Cur composite film can also explain this result. After 3% (w / w) of ZIF-8&CEO nanocrystals were incorporated into the composite film, fine protrusions were observed on the surface of the composite film, and no obvious changes were observed in the cross section. When the amount of nanocrystals added reached 5% (w / w), the surface of the composite film protruded significantly, and obvious pores were observed in the cross section. Further increasing the amount of nanocrystals added would make the above phenomenon more obvious. This may be because a small amount of nanocrystals can be evenly dispersed in the PVA network structure, which will produce a small amount of aggregation, but it does not affect the structure. However, when the amount of nanocrystals added is too large, the dispersion of the nanocrystals is uneven, and obvious aggregation occurs in the network structure.

[0092] Water vapor permeability of the composite film: Briefly, the composite film was covered on a cup (50 ml) filled with 40 g of color-changing silica gel and then sealed with a rubber ring and vacuum grease. The cup was then placed in a desiccator with 3 L of distilled water at the bottom, and the weight of the beaker was recorded every 24 hours for a total of 7 times. The water vapor permeability was calculated according to the following formula:

[0093]

[0094] where Δm is the mass difference of the film between the two measurements (g), d is the thickness of the film (m), and S is the surface area of ​​the exposed film (m 2 ), Δp is the vapor pressure difference across the membrane (Pa), and t is the time interval between two measurements (s). Each type of composite membrane was measured three times.

[0095] Results (corresponding to Figure 4 Middle d): The addition of curcumin did not significantly affect the water vapor permeability of the composite film, which is because curcumin is evenly dispersed in the PVA network structure. However, the addition of ZIF-8 & CEO nanocrystals significantly reduced the WVP of the composite film (155.57 → 138.41 gm -1 s -1 Pa -1 10-12 ), which may be due to the addition of nanocrystals, which reduces the pores of the composite membrane, making it difficult for water vapor to pass through the composite membrane. However, with the increase in the amount of nanocrystals added (3→7% w / w), the excess nanocrystals produce obvious aggregation in the composite membrane, uneven dispersion, and obvious holes in the composite membrane, which reduces the resistance of water vapor passing through the composite membrane and increases the number of paths. The cross-sectional image of the composite membrane can also prove the above point of view. The above results show that loading an appropriate amount of ZIF-8&CEO nanocrystals can make the composite membrane have better water retention properties.

[0096] Water contact angle of the composite film: The water contact angle (WCA) of the composite film was measured using an OCA15EC contact angle meter (Dataphysics, Germany). A 2 μL drop of distilled water was injected into the center of the film surface, and then the surface contact angle was measured using SCA20 software.

[0097] Results (corresponding to Figure 4 e): The WCA of all composite films is less than 60°, which indicates that the composite films have a hydrophilic surface. Among them, the pure PVA film has the lowest WCA value (46.82°), which is due to the abundant hydroxyl groups in PVA. With the addition of curcumin and ZIF-8 nanocrystals, the WCA of the composite film increases significantly, which is related to the hydrophobicity of curcumin and nanocrystals. The addition of hydrophobic materials reduces the number of hydroxyl groups exposed on the surface of the film, thereby enhancing the hydrophobicity of the composite film.

[0098] Moisture content and water solubility of the composite film: Specifically, the composite film was cut into appropriate sizes (2×2 cm) and its initial mass was weighed, and then placed in an 80°C environment for drying for 24 hours, and the sample mass was weighed when it reached equilibrium. The moisture content of the composite film was calculated according to the following formula:

[0099]

[0100] Where w0 is the initial mass of the composite film, and w1 is the mass of the composite film after drying. Three samples of each composite film were prepared for measurement, and the average value was calculated.

[0101] The dried composite film was placed in 8 mL of distilled water and shaken (100 rpm) at 25 °C for 12 h. The composite film was then dried at 80 °C to a constant mass. The water solubility of the sample was calculated using the following formula:

[0102]

[0103] Wherein, w1 is the mass of the composite membrane after initial drying, and w2 is the dry mass of the composite membrane after immersion. Three samples of each composite membrane were prepared for measurement, and the average value was calculated.

[0104] Results (corresponding to Figure 4 fg): Compared with pure PVA film, the composite film loaded with curcumin and nanocrystals has lower water content and water solubility, and the water content and water solubility of the composite film are negatively correlated with the amount of curcumin and nanocrystals added. This is due to the hydrophobicity of curcumin and nanocrystals on the one hand, and the interaction between PVA and additives on the other.

[0105] Mechanical properties of composite films: The tensile strength and elongation at break (EAB) of the composite films were measured by a texture analyzer (TA-XTplus, Stable Micro Systems, UK). The tensile strength and elongation at break of the composite films were calculated according to the following formula:

[0106]

[0107] Wherein, F is the maximum axial tensile force before the composite membrane breaks (N), L0 is the initial length of the composite membrane (mm), d is the thickness of the composite membrane (mm), and L0 is the length of the composite membrane before breaking (mm). Each composite membrane was repeated five times.

[0108] Results (corresponding to Figure 4 (middle): Pure PVA film has the highest tensile strength (24.67MPa) and elongation at break (408.79%), and has strong mechanical properties. With the addition of curcumin and ZIF-8&CEO nanocrystals, it was found that the TS of the composite film decreased, but there was no significant effect on the results. After curcumin was added to the PVA film, the EB value of the composite film decreased from 408.74% to 376.93%. This may be due to the addition of curcumin, which caused the polymer chains to form stacking, enhancing the hardness of the film. However, the increase in the amount of curcumin added did not further affect the EB of the composite film. The introduction of nanocrystals also reduced the EB value of the composite film. When 3% (w / w) nanocrystals were added to the composite film, the EB value of the composite film decreased from 375.41% to 300.33%. This may be due to the dispersion of nanocrystals in the PVA network structure, which affected the stability of the structure. When the amount of nanocrystals added reached 7% (w / w), the EB value of the composite film decreased to 226.14%. This is due to the addition of excessive nanocrystals, which, as shown in the SEM images, produced obvious aggregation in the composite film and destroyed the PVA network structure.

[0109] Composite film preservation experiment (corresponding to Figure 6): Among the 7 composite films, PVA-1.5Cur-3% ZIF8&CEO film was selected to evaluate the fresh-keeping-indicating effect of the composite film on fish meat. Specifically, live grass carp (~2.5 kg) were caught from local fish ponds in May 2024 and immediately transferred to the laboratory. Fresh fish fillets (15±2g) were placed in a culture dish (9cm in diameter), and a composite film of appropriate size (3×3cm) was attached to the inner side of the upper cover of the culture dish. The culture dish was then stored at room temperature (25±2℃), and the apparent changes of the fish meat and the composite film were recorded with a camera, and the color changes of the composite film were recorded using a CR400 colorimeter. At the same time, an automatic Kjeldahl nitrogen analyzer (K1160, Hanon, China) was used to determine the total volatile basic nitrogen (TVB-N) of the fish fillets. The fish meat treated with PVA and PVA-1.5Cur films was used as the control group, and the fish meat without any treatment was used as the blank control group. The color change rate of the composite film was calculated according to the following formula:

[0110]

[0111] Here L i , a i and b i is the initial color parameter of the sample, L c , a c and b c The current color parameters of the sample.

[0112] Results: During storage, fish protein was oxidized and decomposed by microorganisms and endogenous enzymes, producing volatile amines such as ammonia, dimethylamine and trimethylamine. These products are collectively referred to as volatile basic nitrogen (TVB-N), which is an important indicator for evaluating the freshness of fish.

[0113] In order to verify the feasibility of the multifunctional composite film in extending the shelf life of fish and indicating the freshness of fish, we measured the TVB-N value of fish at different storage times and the color value of the corresponding composite film. The TVB-N value of fresh fish was 8.58±0.49mg / 100g. After storage at 4℃ for 9 days, the TVB-N value of the fish in the control group (not treated with the composite film) increased to 25.41±0.81mg / 100g, indicating that the fish had deteriorated (fresh fish standard: TVB-N<20mg / 100g, GB 2733-2015).

[0114] Under the same conditions, the TVB-N values ​​of fish meat treated with PVA film and PVA-1.5Cur film increased to 22.07±0.40mg / 100g and 20.18±0.20mg / 100g, respectively, and they were also spoiled. It is worth noting that the TVB-N value of fish meat treated with PVA-1.5Cur-3% ZIF8&CEO film was 18.75±0.13mg / 100g on the 9th day of storage, which was still fresh and decreased by 26.21% compared with the control group. During the entire storage period, the increase in TVB-N value of the PVA-1.5Cur-3% ZIF8&CEO group was significantly slower than that of the control group. This is attributed to the antibacterial and antioxidant activity of ZIF-8&CEO nanocrystals in the composite film, which delayed the spoilage of fish meat.

[0115] The PVA film showed no obvious color change during the storage of fish, while the PVA-1.5Cur and PVA-1.5Cur-3% ZIF8&CEO films showed significant color changes as the TVB-N value of the fish changed. This is because volatile amines cause the structure of curcumin in the film to change, resulting in color changes. During storage, the color change rate of the PVA-1.5Cur-3% ZIF8&CEO film was significantly higher (p<0.05) than that of the PVA-1.5Cur film, reaching 23.36% and 35.54% on the 9th day, respectively. This may be due to the high specific surface area and strong adsorption of ZIF-8&CEO nanocrystals, which make the composite film more sensitive to volatile amines. Studies have shown that the large pore size of ZIF-8 can effectively adsorb volatile amines.

[0116] In summary, during storage, PVA-1.5Cur-3% ZIF8&CEO film effectively delayed the spoilage of fish meat, and the composite film showed significant color changes as the TVB-N value of fish meat increased during storage. Therefore, PVA-1.5Cur-3% ZIF8&CEO film is suitable for extending the shelf life of fish meat and indicating the freshness of fish meat.

[0117] The method embodiments described above are merely illustrative, and some or all of the steps may be selected according to actual needs to achieve the purpose of the present embodiment. A person of ordinary skill in the art may understand and implement the method without creative effort.

[0118] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a fresh-keeping material based on nanocrystals, characterized in that: include: Dissolving zinc nitrate hexahydrate in deionized water to obtain an aqueous solution, dissolving 2-methylimidazole in methanol to obtain a methanol solution, adding plant essential oil to the methanol solution, and fully dissolving the aqueous solution and the methanol solution respectively; The aqueous solution is dripped into the methanol solution, and the mixture is subjected to magnetic stirring and then centrifuged to obtain a precipitate, and the precipitate is washed several times and then freeze-dried to obtain nanocrystals; Add polyvinyl alcohol into distilled water, stir until completely dissolved, then add glycerol as a plasticizer and continue stirring to obtain a polyvinyl alcohol solution; The nanocrystals are added to the polyvinyl alcohol solution, calcium chloride and distilled water are added after thorough mixing, and a film-forming solution is obtained after thorough stirring. The film-forming solution is poured into a polystyrene culture dish and dried to obtain a composite film.

2. The method for preparing a fresh-keeping material based on nanocrystals according to claim 1, characterized in that: The plant essential oil includes clove essential oil.

3. The method for preparing a fresh-keeping material based on nanocrystals according to claim 1, characterized in that: The method further comprises adding curcumin to the polyvinyl alcohol solution before adding calcium chloride and distilled water after the thorough mixing.

4. The method for preparing a fresh-keeping material based on nanocrystals according to claim 1, characterized in that: The step of fully dissolving the aqueous solution and the methanol solution respectively comprises: The aqueous solution and the methanol solution are respectively subjected to ultrasonic treatment at room temperature until the solutions are fully dissolved.

5. The method for preparing a fresh-keeping material based on nanocrystals according to claim 1, characterized in that: The step of washing the precipitate several times comprises: The precipitate was washed several times with methanol.

6. The method for preparing a fresh-keeping material based on nanocrystals according to claim 1, characterized in that: Before the film-forming solution is poured into a polystyrene petri dish and dried, the method further comprises: The membrane-forming solution is ultrasonically treated at room temperature to remove bubbles in the solution and to uniformly disperse the components.

7. The method for preparing a fresh-keeping material based on nanocrystals according to claim 1, characterized in that: The mass percentage of glycerol is 30% of polyvinyl alcohol.

8. The method for preparing a fresh-keeping material based on nanocrystals according to claim 3, characterized in that: The mass ratio of the curcumin is 0.5-1.5% of the polyvinyl alcohol.

9. The method for preparing a fresh-keeping material based on nanocrystals according to claim 1, characterized in that: The nanocrystals are added to the polyvinyl alcohol solution, and the mass ratio of the nanocrystals is 3% to 7% of the polyvinyl alcohol.

10. The method for preparing a fresh-keeping material based on nanocrystals according to claim 1, characterized in that: The mass ratio of calcium chloride is 4% of polyvinyl alcohol.